A financing mode of Urban Rail transit based on land value capture: A case study in Wuhan City. (July 2017) - Sun, Jun; Chen, Tian; Cheng, Zuchen; Wang, Cynthia C.; Ning, Xin
Abstract: While urban rail transit has gained increasing popularity, there are still many problems related to obtaining financial resources for constructing it in China. It is proved that the Land Value Capture (LVC) theory can provide theoretical support for exploring new financing mode of urban rail transit to solve these problems. This paper reviews the concept of LVC and the existing LVC finance mechanisms, in particular, Joint Development (JD) . It is revealed that JD can't be directly copied and reproduced in mainland China. The characteristics of land acquisition policy as well as the practice of rail transit construction in mainland China are summarized, and based on the findings, the Predetermined Land Reserve Mode (PLR) is proposed. The essence of this proposed mode is to link the reserve of specific land parcels with the relevant rail transit project and ensure it benefits from the predetermined land reserve. Rail transit companies, with the authorizations from the government, can reserve suitable land parcels prior to the planning and construction of the rail transit system so that they can capture the increased land value after the land transfer. PLR is a new finance mechanism based on LVC and it is different from JD under comparative analysis. Analytical results show that PLR has unique advantages. To demonstrate the performance of PLR, a case study of constructing the urban rail transit system in Wuhan City, China, is presented in this paper, and it shows that the PLR is well suited for financing the urban railway systems in cities of mainland China. Highlights: The barriers in the application of Joint Development in China were analyzed. A new financing mode of urban rail transit–Predetermined Land Reserve was proposed. The implementation process and key points of Predetermined and Reserve were analyzed. Differences between Joint Development and Predetermined Land Reserve were analyzed. A case study in China showed the feasibility of Predetermined Land Reserve.